Fostering Sustainable Service For Disabled Communities Through Youth Volunteerism: An Analysis Of Key Characteristics Using Fuzzy Delphi Methodology - Noornajihan Ja‘afar; Nurul Asiah Fasehah Muhamad; Norakyairee Mohd. Raus; Siti Fatimah Mohd Tawil; Nusairah Ramli; Syed Najihuddin Syed Hassan; Nik Ahmad Farid Nik Shabery (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA